G570(P) Project play – medical students providing out of hours play for paediatric patients. (27th April 2015) - Pearson, H; Harlin-Bethel, L; Shea, T
Abstract : Context: This study examines the effectiveness of Project Play; a collaboration between medical students and health play specialists in order to provide an out of hours play service at The Royal London Hospital (RLH). Problem: There is no out of hours play for children, and there is not enough clinical attachment time for medical students on paediatrics. Assessment of problem and analysis of its causes: The Play Department is currently only able to provide patients with a service Monday to Friday 9–5 pm. The patients need to have access to therapeutic play outside of these hours, however due to staffing we are unable to provide this service. Students have expressed a high level of interest in paediatrics and a recurrent comment is that there is not enough time in the core module provided for paediatric clinical attachments. Dissatisfaction is show in this quote from the head of the Human Development module: "Although students have expressed a high level of satisfaction with the Paediatric modules in their Human Development course, a recurrent comment is that there is not enough time in the core module provided for all students. Ours is one of the shortest clinical attachments of UK medical schools." Intervention: All volunteers were required to attend a training day. Then, two volunteering session a week were initiated in October 2014. These ran 6–8 pm on Tuesday and Thursday evenings. Tuesday sessions were aimed at children aged 3–12 years, Thursday 12–18 years. The number of volunteers at each session ranged from 4 to 7. There is one lead volunteer from the committee at each session. Measurement of improvement: Effects of changes: The patients, parents and staff have been very positive towards One of the regular patients: ' I love Project Play, all the people are so nice and we do something different each week. I can't believe doctors would want to play with me! ' One of the most positive aspects of 'Project Play' has been noted by one of the senior nurses who said: ' We had a patient the other day who needed an NG tube passed and was refusing, when she heard she wouldn't be able to participate in 'project play' until it was in she laid completely still and let us do it so she didn't miss a minute. It is amazing !' An anonymous questionnaire was carried out and 22 responses were received (Table 1 ). Students have learnt to overcome tough communication barriers and make last minute adaption's to play in order to incorporate all children regardless of physical conditions. A key component of Project Play is 'teen club' which runs once a week, a number of volunteers expressed apprehension at the thought of entertaining a group of teenagers, however, many have found teen club to be rewarding and particular beneficial for developing their communication skills. Lessons learnt: Project play recruits medical students from all years of study, therefore, there is variation in clinical knowledge. We believed this to be appropriate because we are not providing any clinical care, however a few issues have arose from this. It is vital that MDT members assume that we have no clinical knowledge in order to avoid mistakes i.e. CF patients that can't mix together. Message for others: Ultimately we have found project play to be a positive experience for medical students and have ambitions to make it part of the medical school curriculum. ' It really felt like the children were enjoying a rare chance to socialise and have fun without feeling like they were ill and in hospital .